Triggered chain reaction: The meanings of symptom clusters for patients with chronic obstructive pulmonary disease: A cross-sectional qualitative study - Fei Fei; Richard J. Siegert; Xiaohan Zhang; Jonathan Koffman (PLoS ONE, 2026)
Purpose Symptoms in chronic obstructive pulmonary disease (COPD) commonly co-occur as ‘symptom clusters’, yet little is known about how patients interpret and make sense of these experiences. This study aimed to explore the meanings patients with COPD attribute to symptom clusters, their impact on health-related quality of life, and the strategies used to manage them. Methods A qualitative study using semi-structured interviews was conducted with a purposive sample of 30 patients with COPD recruited from a university teaching hospital in China. Data were analysed using the Framework approach, informed by the Theory of Unpleasant Symptoms and the concept of biographical disruption. Results Three interrelated themes were identified. First, participants understood symptom clusters as dynamic, interacting experiences, often organised around “trigger symptoms” (e.g., cough precipitating breathlessness and fatigue), rather than as isolated symptoms. Second, these clusters disrupted multiple dimensions of everyday life, including physical functioning, social participation, and sense of self. Third, participants actively negotiated symptom burden through a range of adaptive strategies, prioritising symptoms based on their perceived meaning and impact rather than clinical severity. These findings highlight how symptom experiences are shaped by both physiological interconnections and personal interpretations. Conclusions This study provides novel insight into how people with COPD experience symptom clusters as interconnected, meaning-laden phenomena. Recognising the role of “trigger symptoms” and patients’ subjective prioritisation of symptoms has important implications for person-centred assessment and supports the development of targeted, mechanism-informed approaches to symptom management in COPD. I can’t walk long distances. I can’t go out and spend time with my friends. This is a big problem in my life. (69-year-old male, GOLD stage III) Other people can run around. They visit relatives or friends during the holidays. I can’t. I cough all day long and can only stay at home. (63-year-old female, GOLD stage IV)